Pemuda Sebagai Poros Perkembangan : Peran Pemuda dalam Perjuangan Indonesia dan Penyebaran Agama Islam - Wahyuni, Tri (Maliki Interdisciplinary Journal, 2024)
The role of Indonesian youth began to increase when there was a planning meeting between all youth organizations representing various regions in Indonesia in the past, which then formed the Youth Pledge. The youth figures who were the pioneers in the formation of the Youth Pledge became examples or role models that can be emulated by today’s young generation so that they are able to play an active role without thinking only about personal gain but also thinking about the interests of the unitary Republic of Indonesia which has been independent for 79 years. A country is considered to be developing when it is able to optimize the abilities of its youth in order to create a country that is self-sufficient and improves the conditions of its people. Likewise, in the spread of Islam in the archipelago, in the history of the spread of Islam, youth have also had many active roles from before independence until now where young people tend to easily accept new teachings that suit their conditions and are able to easily understand the current conditions of the country. where he lives. Youth have the most important role in maintaining all stability, both religious and state, this is due to the high population size and their understanding which is considered to be able to differentiate between wrong and right things but can still be influenced by other factors so that they can be easily mobilized to meet a particular need. organizations that utilize their capabilities.